(untitled) (Medical Forum Monthly, 2024)
Objective: It is only natural to assume that the course of disease is more aggressive in the face of 25-Hydroxy vitamin D deficiency the prognosis of patients presenting with congestive heart failure would be grim. More important so, their quality of life during the years that they live would be markedly reduced. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the Department of Cardiology, Liaquat University of Medical & Health Sciences, Jamshoro during the month of May 2016. Materials and Methods: Forty patients (chosen via purposive sampling) presenting with congestive heart failure were included in the study. Data was derived using a structured interview based questionnaire after taking written informed consent. Investigations were also carried out to determine the levels of 25-hydroxy vitamin D levels in the blood. The patient condition and the quality of life was investigated at the time of discharging the patient and comparison was drawn. Results: Sixty percent of the patients were men, while the remaining forty percent were women. The ratio of the patients with or without 25-hydroxy vitamin D deficiency was 1:1 and the patients with 25-hydroxy vitamin D deficiency were experiencing markedly low levels of quality of life due to aggravated disease. Conclusion: The deficient levels of 25-hydroxy vitamin D, as indicated in literature, alter the metabolism of minerals and lead to myocardial dysfunction in the congestive heart disease patients. It is thus an aggravating factor for pathogenesis of congestive heart failure and leads to marked decrease in the quality of life.